CYBER COUNSELING ASSISTED WITH FACEBOOK TO REDUCE ONLINE GAME ADDICTION - Prasetiawan, Hardi (Universitas Muhammadiyah Metro, 2016)
Cyber counseling is divided into various shapes, one form is the use of facebook. Guidance and counseling teacher in schools can implement the cyber counseling assited with facebook to reduce online game addiction the students who are more likely to prefer to communicate by text relationship, and students who do not feel comfortable with counseling services by face to face. Problems of children who are addicted Online Games at school require a relief to effort with Group Counseling assited with facebook services for addressing and alleviating the problems experienced, both personal and social through cyber counseling. The positive impact of service delivery cyber counseling assited with facebook is not out of the role from well counselors as providers to service with the active role of students while finding information on social media like Facebook, so socializing continually needs to be implemented furtherKeyword : Cyber Counseling, Facebook, Online Game Addiction